Utilization of the finite element method for the calculation and examination of underground power cable ampacity - Mahmood Khalid Hadi (Institute of Advanced Engineering and Science, 2019)
Currently, the use of underground electric cables is a regular feature of present-day power transmission and distribution schemes. Issues related to economical limitations and the lack of adequate space led to the need for cables with an elevated current carrying capacity (ampacity). In order to achieve this objective, public services around the globe are focusing not only on better designs, but also on improving the level of precision in the context of cable parameter values. Precise parameter values are essential for ensuring that the replicated outcomes correspond sufficiently close to actual circumstances. While the conventional approach to ampacity calculation is through the IEC-60287 procedure, the numerical route is considered more specific and flexible. This endeavour harnesses the finite element method to conceive an innovative process for calculating the thermal field and ampacity of a cable. This process involves the crafting of a temperature field distribution model for scrutinizing temperature distribution in the region of an electric cable, and the deployment of the linear interpolation procedure for computing its ampacity. Subsequent to its formation, the model was put into operation on the underground cable 33KV XLPE.